Health technologies for the education of individuals with intestinal stoma: a scoping review - Assis Afonso, Gustavo; Monteiro de Jesus Maldonado, Daniele; de Medeiros Escobar, Lana; Ferreira Dias, Thayná; Valéria Dantas de Oliveira Souza, Norma; Cabral Pereira da Costa, Carolina (Estima – Brazilian Journal of Enterostomal Therapy, 2026)
Objective: To map the scientific evidence related to health technologies aimed at the education of adults and older adults with intestinal stoma in the hospital setting. Method: A scoping review conducted in accordance with the recommendations of the JBI and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses – extension for Scoping Reviews. Studies conducted by nurses, in any language, without time restrictions, and with different methodological designs were included. Searches were carried out in five databases. Data were based on thematic and statistical analyses. Results: The studies highlighted multiple technologies for individual education, such as verbal instructions, printed textual materials, multimedia resources, demonstrations, and hands-on practices focused on self-care, etc. Conclusion: The technologies adopted for the development of the teaching-learning process are organized in diverse formats. These tools are essential for disseminating knowledge and promoting self-care, contributing to improvements in the context of health promotion, prevention, and rehabilitation. This study provided a synthesis of existing educational resources, supporting nursing professional practice through the mapping and analysis of their applications.